2017
DOI: 10.1016/j.medici.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sputum culture conversion in patients with pulmonary tuberculosis

Abstract: The most important factors in predicting sputum culture conversion after 1 month of treatment were grades of acid-fast bacilli in sputum smears at time of diagnosis and scores of SGRQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Furthermore, while most patients are cured and remain free of TB upon the completion of a 6-month treatment regimen, some patients relapse even if they were fully adherent to treatment (7). To date, this interpatient variability in treatment responses has primarily been attributed to differences in host factors such as baseline mycobacterial loads, the presence of cavitary lesions, HIV infection, and smoking (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while most patients are cured and remain free of TB upon the completion of a 6-month treatment regimen, some patients relapse even if they were fully adherent to treatment (7). To date, this interpatient variability in treatment responses has primarily been attributed to differences in host factors such as baseline mycobacterial loads, the presence of cavitary lesions, HIV infection, and smoking (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the poor scientific evidence, clinical guidelines cannot provide a clear recommendation about the isolation period, although some authors recognize a typical conversion period between 30 and 60 days [16] , [17] . Other guidelines suggest that respiratory isolation could be discontinued 2 to 3 weeks after the initiation of treatment if there is clinical improvement, low risk of resistance, and evidence of good therapeutic compliance [18] , [19] , [20] , although these recommendations differ in several publications that have determined that approximately 40–60% of patients could be contagious after one month of initiating treatment [5] , [21] , [22] . These studies included patients with various nationalities (European, African, Asiatic, and Latin American) and comorbidities (HIV, DM, chronic bronchopathy, tobacco, and alcohol consumption), and in line with this data, in our investigation, 41% of patients remained culture positive at 4 weeks, a fact that supports the generalization of the score in subjects with different characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial conducted in Ethiopia, daily supplementation with vitamin D could ameliorate TB symptoms but it played no role in sputum smear conversion [22]. A recent study in Lithuania also concluded that the sputum culture conversion rate in TB patients was not associated with serum vitamin D levels at baseline [23].…”
Section: Discussionmentioning
confidence: 99%